1991
DOI: 10.1177/000331979104200802
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Angioplasty and Diagnostic Catheterization: Safe and Effective but Riskier in Unstable Angina

Abstract: Percutaneous transluminal coronary angioplasty was performed at the time of the diagnostic catheterization in 188 patients (215 lesions) at a University Hospital in order to assess the efficacy of this approach and the potential role it should play in the evaluation and treatment of patients. Patients either presented for diagnostic catheterization for evaluation of stable coronary disease (79 patients) or for unstable or new onset anginal symptoms (109 patients). Lesions were graded as to whether they were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Accordingly, patients with unstable or progressive symptoms of myocardial ischemia are appropriate candidates for ad hoc PCI. Although earlier studies suggested complications were higher in unstable patients treated by the ad hoc strategy [5,9], more recent data suggest that rapid triage of unstable patients to the catheterization laboratory with aggressive antithrombotic therapy followed by ad hoc PCI results in superior 30-day outcomes compared to prolonged antithrombotic treatment for 3-5 days before angiography [20].…”
Section: Unstable Patientsmentioning
confidence: 98%
See 3 more Smart Citations
“…Accordingly, patients with unstable or progressive symptoms of myocardial ischemia are appropriate candidates for ad hoc PCI. Although earlier studies suggested complications were higher in unstable patients treated by the ad hoc strategy [5,9], more recent data suggest that rapid triage of unstable patients to the catheterization laboratory with aggressive antithrombotic therapy followed by ad hoc PCI results in superior 30-day outcomes compared to prolonged antithrombotic treatment for 3-5 days before angiography [20].…”
Section: Unstable Patientsmentioning
confidence: 98%
“…Nine studies examined ad hoc balloon angioplasty before stenting became the dominant procedure [1][2][3][4][5][6][7][8][9]. Among these studies, 12-83% of the PCIs were classified as ad hoc.…”
Section: Ad Hoc Versus Separate Pci In Prestent Eramentioning
confidence: 99%
See 2 more Smart Citations
“…During the past several years, in an effort to reduce hospital length of stay and potentially reduce costs, PCI has increasingly been performed immediately after the diagnostic coronary angiographic procedure (811), with reported incidence ranging from 52% to 83% (812)(813)(814). The indications for diagnostic catheterization and coronary angiography in different catheterization laboratory settings are discussed in the ACC/SCAI Expert Consensus Document on Catheterization Laboratory Standards (Table 28) (309,815).…”
Section: Ad Hoc Angioplasty-pci At the Time Of Initial Cardiac Cathetmentioning
confidence: 99%